Association between urinary polycyclic aromatic hydrocarbon metabolites and dyslipidemias in the Chinese general population: A cross-sectional study. (February 2019) - Ma, Jixuan; Zhou, Yun; Liu, Yuewei; Xiao, Lili; Cen, Xingzu; Li, Wei; Guo, Yanjun; Kim, Myongho; Yuan, Jing; Chen, Weihong
Abstract: Background: Exposure to polycyclic aromatic hydrocarbons (PAHs) has been associated with metabolic diseases. However, relationships between PAH exposures and dyslipidemias have not been well addressed. Objectives: To investigate associations between urinary PAH metabolite concentrations and dyslipidemias in the general population. Methods: Twelve urinary PAH metabolites and four serum lipid profiles were measured in 3640 Chinese adults from the Wuhan-Zhuhai cohort. Dyslipidemias, including hyper-total cholesterol (HyperTC), hyper-triglyceride (HyperTG), hyper-low density lipoprotein cholesterol (HyperLDL-C), and hypo-high density lipoprotein cholesterol (HypoHDL-C) were classified according to the levels of serum lipids. Multiple logistic regression models were used to estimate the associations between urinary PAH metabolites and the prevalence of dyslipidemias. The effects of PAH exposure routes on dyslipidemias were further estimated by stratified analysis. Results: We found positive exposure-response relationships between urinary PAH metabolites and the prevalence of dyslipidemias. Compared with the lowest tertile of urinary PAH metabolites, increased risk of HyperTC were observed in those in the highest tertiles; The odds ratios (ORs) and 95% confidence intervals were 1.23 (1.03, 1.47), 1.44 (1.21, 1.71), 1.19 (1.01, 1.42), and 1.43 (1.20, 1.71) for 1-OHNa, 9-OHFlu, 1-OHPh, and 4-OHPh, respectively. Participants in the highest tertiles of 1-OHNa and 2-OHFlu had higher risk for HyperLDL-C, and the ORs were 1.21 (1.01, 1.45) and 1.18 (0.98, 1.42), respectively. Among smokers, only urinary 1-OHNa was associated with increased risk of HyperTC (1.36, 1.08–1.73) and HyperLDL-C (1.33, 1.01–1.74). While the increasing urinary levels of 9-OHFlu, 1-OHPh, and 4-OHPh were significantly associated with increased risk of HyperTC among non-smokers. In addition, the associations between urinary PAH metabolites and dyslipidemias were more pronounced among non-smokers who are cooked for themselves and had long-term traffic exposure. Conclusion: Elevated urinary PAH metabolites were associated with increased risks of HyperTC and HyperLDL-C. The source of PAH exposure could modify PAH species that affect dyslipidemias. Graphical abstract: Highlights: Urinary PAH metabolites were measured in general population of China. Significant relationships were observed between the urinary PAH metabolites and the prevalence of dyslipidemias. The source of PAH exposure could modify PAH species that affect dyslipidemias.